Special Issue on Silicate Solid Waste Recycling - Xiao, Yue; Yunusa, Mujaheed; Jelagin, Denis; Tan, Hongbo; Strnadel, Bohumír (Materials (Basel, Switzerland), 2021)
The reuse of industrial silicate solid wastes, including fly ash, slag, and waste rubber, is one of the most significant environmental and economic concerns worldwide [...].